The Effect of Affective Commitment on Task Quality: Mediating Role of Employee Engagement - Dewi Kania (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2023)
This study aims to examine the influence of Affective Compliance on Task Quality, with a specific focus on the potential mediating effect of Employee Engagement. Affective Compliance pertains to the degree of emotional connection that employees experience towards their employing organization. In contrast, Task Quality refers to the extent to which the output generated by employees aligns with predetermined criteria and anticipated outcomes. The research employs the Partial Least Squares (PLS) data analysis method, which facilitates the modeling of intricate relationships among the variables under investigation. The study's findings indicate that Affective Compliance exerts a positive and statistically significant impact on Task Quality. However, the discovery that Employee Engagement serves as a mediator in the association between Affective Compliance and Task Quality is of greater interest. Employee engagement is a concept that aids in elucidating the relationship between affective Compliance and task quality. The findings of this study carry significant implications for the fields of human resource management and organizational development. Enhancing employees' levels of affective Compliance can enhance the quality of their tasks by fostering increased employee engagement. Hence, organizations must prioritize strategies that enhance the emotional connection between employees and the company, thereby enhancing the work output's quality. This study offers a comprehensive analysis of the interconnectedness of these variables within the work setting, presenting the possibility of enhancing employee productivity and work quality.